INNOVATIVE FACTORS OF INCREASING THE COMPETITIVENESS OF RETAIL CHAINS IN UKRAINE - KUZMENKO, Olena; KRUL, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article provides a comprehensive analysis of the innovative factors that determine the competitiveness of retail chains in Ukraine in the context of digital transformation, globalization, and growing market turbulence. The study identifies and explores the main directions of innovative development, including the digitalization of business processes, implementation of omnichannel strategies, automation and robotization of operations, adoption of advanced logistics technologies, as well as environmental and social initiatives. Specific innovative practices of leading Ukrainian retail chains such as “Silpo,” “ATB,” “Novus,” and “METRO Ukraine” are analyzed in detail. These practices cover both technological solutions (e.g., AR/VR in-store experiences, mobile applications, digital loyalty programs) and organizational changes (new retail formats, supply chain optimization). The article also identifies key barriers to innovative development, such as limited access to financing, low levels of digital literacy among staff, outdated IT infrastructure, regulatory constraints, and resistance to change within companies. Strategies to overcome these barriers are proposed, including investments in human capital, modernization of infrastructure, and enhanced cooperation between the state and the business sector. The findings highlight that innovation is a decisive factor for strengthening market positions and achieving sustainable competitive advantages in the retail sector. They can be applied to develop effective strategies for sustainable growth, ensuring that retail chains remain adaptive and resilient in the face of economic instability and evolving consumer demands. This research contributes to both theoretical understanding and practical guidance for retail business leaders, policymakers, and scholars interested in the dynamics of innovation-driven competitiveness in emerging markets.
Keywords: innovations; competitiveness; retail chains; digital transformation; omnichannel; automation; logistics